Adaptation Approaches to Sea-Level Rise in Florida - Ondine Wells; Whitney Gray; Paul Monaghan (EDIS)
There is consensus among the scientific community that climate change is occurring and will have far-reaching effects on our global ecosystems and human systems. In Florida, adaptation to climate change is occurring in both natural and human systems. As coastal communities prepare for sea-level rise, they can use several strategies to integrate natural adaptation processes into their planning processes. By taking a proactive approach to adaptation rather than a reactive one, communities will be able to better protect the resources upon which they depend. This 4-page fact sheet was written by Ondine Wells, Whitney Gray, and Paul Monaghan, and published by the UF Department of Agricultural Education and Communication, July 2014.